On the Shock Source of Sustained Gamma-Ray Emission from the Sun. (November 2019) - Gopalswamy, N; Mäkelä, P.; Yashiro, S.; Lara, A.; Akiyama, S.; Xie, H.
Abstract: It has recently been shown that the spatially and temporally extended γ-ray emission in solar eruptions are caused by >300 MeV protons precipitating on the Sun from shocks driven by coronal mass ejections (CMEs). The γ-rays result from the decay of neutral pions produced in the proton-proton interaction when the >300 MeV protons collide with those in the chromosphere. The evidence comes from the close correlation between the durations of the sustained gamma-ray emission (SGRE) and the associated interplanetary (IP) type II radio bursts. In this paper, we provide further evidence that support the idea that protons accelerated in IP shocks driven by CMEs propagate toward the Sun, precipitate in the chromosphere to produce the observed SGRE. We present the statistical properties of the SGRE events and the associated CMEs, flares, and type II radio bursts. It is found that the SGRE CMEs are similar to those associated with ground level enhancement events. The CME speed is well correlated with the SGRE fluence. High CME speed is an important requirement for the occurrence of SGRE, while the flare size is not. Based on these results, we present a schematic model illustrating the spatially and temporally extended nature of SGRE related to the CME flux rope-shock structure.